Implementation of Reading Fixed ‘Do’ and Moving ‘Do’ Notations on Improving Music Practical Achievement - Heri Murbiyantoro; Budi Dharmawanputra; Raden Roro Maha Kalyana Mitta Anggoro; Harpang Yudha Karyawanto; Marda Putra Mahendra (Universitas Negeri Medan, 2024)
Music education is a realm of study concerned with the teaching and learning of music. This music education will develop affective, motor skills in students who play instruments and expand cognitive development through reasoning and interpretation of musical notation. However, many people still underestimate music education. In the education and teaching system of music arts, especially in the last years of the 20th century, new methods emerged. One of the methods that will be discussed is the Tonika-Do Method. This article is a type of literature study and uses the exposition method in presenting the concepts contained in previous studies. The sources used contain the results of discussions about art education, music, and music education. The application of fixed